248 An Evaluation of Patient Education Post-Stroke. (16th September 2019) - Morrison, Laura; McAteer, Claire; Donaghy, Lisa; O'Connor, Marie; Dolan, Eamon
Abstract: Background: In 2018, 212 acute strokes were diagnosed in our university teaching hospital. Our stroke service is evolving to meet the needs of this growing population. The aim of this study was to evaluate the knowledge patients have about their stroke diagnosis and identify how to improve education given post-stroke. Methods: Thirty consecutive patients attending stroke clinic completed a questionnaire, including questions regarding aetiology of their stroke, medications started, driving and education received as an inpatient. Results: The thirty patients were a median of 16 months post-stroke. One had a haemorrhagic stroke, all others ischaemic stroke. Only 33% correctly described the type of stroke they had. 50% correctly identified all the risk factors they had been diagnosed with, including atrial fibrillation, hypertension, hypercholesterolaemia and carotid stenosis. 70% of patients reported receiving education in hospital post-stroke. Of these, 13% received written information. 30% of patients were shown their brain scan and the majority (89%) found it beneficial. 71% of those who did not see their scan would have liked to. 52% reported knowing which medications had been started post-stroke but only 23% of patients listed new medications correctly. 43% of patients felt they did not receive enough information about new medications and 27% reported either sometimes or frequently missing medications. 77% of patients drove before their stroke. 74% of these reported that they were advised not to drive post-stroke. Of these, 35% correctly identified how long they were advised not to drive for. Only 26% of those driving before their stroke had driving advice in their discharge letter. Conclusion: These results illustrate areas in which we can improve education post-stroke, including ensuring patients receive individualised information about the aetiology of their stroke, risk factors and the importance of new medications. It also highlights the importance of ensuring advice regarding driving is clearly explained and documented.